Life in Kierkegaard's Imaginary Rural Parish: Preaching, Correctivity, and the Gospel - Edwards, Aaron (Toronto journal of theology, 2014)
What kind of pastor might Søren Kierkegaard have been? What kind of gospel would he have preached? Kierkegaard's polemical theology often portrays him as the perpetually pessimistic legalist, seemingly devoid of grace. This claim will be questioned by situating Kierkegaard's corrective thought in the context of the "imaginary" rural pastorate to which he (occasionally) felt called. Unpacking Kierkegaard's curious reflections on theological correctivity regarding Luther, we find his homiletical imperatives may assist theological and pastoral reflection upon the announcement, reception, and outworking of the gospel in the life of the congregation.